The surface properties of nanoparticles determine the agglomeration state and the size of the particles under physiological conditions - Bantz, Christoph; Koshkina, Olga; Lang, Thomas; Galla, Hans-Joachim; Kirkpatrick, C. James; Stauber, Roland H.; Maskos, Michael (Beilstein Journal of Nanotechnology, 2014)
Due to the recent widespread application of nanomaterials to biological systems, a careful consideration of their physiological impact is required. This demands an understanding of the complex processes at the bio–nano interface. Therefore, a comprehensive and accurate characterization of the material under physiological conditions is crucial to correlate the observed biological impact with defined colloidal properties. As promising candidates for biomedical applications, two SiO2-based nanomaterial systems were chosen for extensive size characterization to investigate the agglomeration behavior under physiological conditions. To combine the benefits of different characterization techniques and to compensate for their respective drawbacks, transmission electron microscopy, dynamic light scattering and asymmetric flow field-flow fractionation were applied. The investigated particle systems were (i) negatively charged silica particles and (ii) poly(organosiloxane) particles offering variable surface modification opportunities (positively charged, polymer coated). It is shown that the surface properties primarily determine the agglomeration state of the particles and therefore their effective size, especially under physiological conditions. Thus, the biological identity of a nanomaterial is clearly influenced by differentiating surface properties.
Keywords: nanomaterial characterization; physiological conditions; surface properties; silica nanoparticles; siloxane nanoparticles